Sir Augustus John Foster papers - Foster, Augustus John, Sir, 1780-1848.
Volumes containing correspondence, diaries, and writings chiefly concerning Foster's assignment as a British diplomat to the United States prior to the War of 1812, and to two present-day cities of Italy, Naples (Kingdom of the Two Sicilies), circa 1802-1804, and Turin (Kingdom of Sardinia), 1824-1840. Correspondence is primarily between Foster and his mother, Elizabeth Cavendish, Duchess of Devonshire. Writings include a five-volume draft entitled, "Notes on the United States of America."
British minister to the United States.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Devonshire, Elizabeth Cavendish, -- Duchess of, -- 1758-1824 -- Correspondence; Great Britain -- Foreign relations -- Italy -- Kingdom of the Two Sicilies; Great Britain -- Foreign relations -- Italy -- Sardinia; Great Britain -- Foreign relations -- United States; Kingdom of the Two Sicilies -- Foreign relations -- Great Britain; Sardinia (Italy) -- Foreign relations -- Great Britain; United States -- Description and travel; United States -- Foreign relations -- Great Britain; Diplomats -- Great Britain